Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Dalam Menggunakan Produk Pembiayaan Musyarakah Di Bank Syariah Indonesia (BSI) Gatot Subroto Di Kota Jambi - Widodo; Bambang Kurniawan; Refky Fielnanda (JOURNAL SAINS STUDENT RESEARCH, 2023)
This thesis aims to reveal the Factors Influencing Customer Decisions in Using Musyarakah Financing Products at Bank Syariah Indonesia (BSI) Gatot Subroto in jambi city. This thesis uses a quantitative approach using a multiple regression statistical analysis method partially and simultaneously with a sample of 75 customers. The research carried out obtained the following results and conclusions: Partially the independent variable Psychological Factor (X1) affects customer decisions (Y) because the musyarakah financing product is in accordance with customer needs, the terms offered are relatively easy and increase customer confidence in Allah and the products offered better; Situational factors (X2) affect customer decisions (Y) because the place is easy to reach in the city center, using musyarakah financing because the time given is so disciplined and musyarakah financing is due to the use of products that suit their needs and uses and the employees are kind and considerate to customers; Social factors (X3) affect customer decisions (Y) because anyone can apply for this financing and provide benefits to the community. The public has also believed in BSI and customers have also seen the advertisements promoted on the banners. Simultaneously (F test) shows that F count (74,679) > F table (2,73) and significant value (0.000) < a (0.05), then Ho is rejected and Ha is accepted, meaning that Psychological Factors (X1), Situational Factors (X2) and Social Factors (X3) simultaneously or simultaneously influence the customer's decision to use the Musyarakah financing product at Bank Syariah Indonesia (BSI) Gatot Subroto because a sense of trust has been created and the distance traveled by the customer is close to home and the information provided received accurately and reliably.